Chemical composition, phytotoxic potential, biological activities and antioxidant properties of Myrcia hatschbachii D. Legrand essential oil - Larissa Junqueira Gatto; Natasha Tiemi Fabri; Angela Maria de Souza; Natasha Stopinski Triaquim da Fonseca; Alethéia dos Santos Furusho; Obdulio Gomes Miguel; Josiane de Fatima Gaspari Dias; Sandra Maria Warumby Zanin; Marilis Dallarmi Miguel (Universidade de São Paulo, 2020)
Myrcia hatschbachii D. Legrand (Myrtaceae) is a native and endemic species from Brazil. This study investigated the essential oil composition, phytotoxic potential, in vitro toxicity, antioxidant properties and antibacterial activity of species. Chromatographic analysis of essential oil identified trans-calamanene, (E)-caryophyllene and spathulenol as major components. Antioxidant capacity was determined by the DPPH• scavenging method and phosphomolybdenum complex formation assay. Antibacterial activity was evaluated using the Minimal Inhibitory Concentration test, demonstrating that the essential oil was active toward Enterococcus faecalis and Staphylococcus aureus. Phytotoxic activity of essential oil was analyzed by testing interference on germination and growth of Lactuca sativa, demonstrating significant inhibition of the hypocotyls and radicles of seeds. Preliminary toxicity studies were determined using Artemia salina, resulting in an LC50 of 409.92 µg/mL, and through hemolytic activity. The results of the phytotoxic activity point to a possible application for Myrcia hatschbachii in the development of natural herbicides and the in vitro toxicity assays suggests the performance of antitumoral activity tests, having in mind the prospection of antineoplastic drugs.